2019
DOI: 10.1002/ajim.23021
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and drug‐related mortality following occupational injury

Abstract: Background Drug overdoses and suicides have been rising since 2000 and are major contributors to a 3‐year decline in US life expectancy. Studies suggest that injured workers have elevated rates of depression and opioid use, but no studies have measured excess mortality related to these risks. Materials and methods We linked New Mexico workers' compensation data for 100 806 workers injured in 1994 through 2000 with Social Security Administration earnings and mortality data through 2013 and National Death Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 37 publications
(47 reference statements)
5
43
0
Order By: Relevance
“…We also found an association between work‐related disability and fatal drug overdoses involving opioids. Applebaum et al recently reported the results of a follow‐up study from the New Mexico workers’ compensation cohort which found an HR of 2.63 (95% CI = 1.91‐3.64) for combined drug‐related and suicide mortality among women and an HR of 1.42 (95% CI = 1.13‐1.79) among men comparing lost‐time to no lost‐time injuries. Circulatory disease mortality was also elevated for men with an HR = 1.25 (95% CI = 1.05‐1.50) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found an association between work‐related disability and fatal drug overdoses involving opioids. Applebaum et al recently reported the results of a follow‐up study from the New Mexico workers’ compensation cohort which found an HR of 2.63 (95% CI = 1.91‐3.64) for combined drug‐related and suicide mortality among women and an HR of 1.42 (95% CI = 1.13‐1.79) among men comparing lost‐time to no lost‐time injuries. Circulatory disease mortality was also elevated for men with an HR = 1.25 (95% CI = 1.05‐1.50) .…”
Section: Discussionmentioning
confidence: 99%
“…Applebaum et al recently reported the results of a follow‐up study from the New Mexico workers’ compensation cohort which found an HR of 2.63 (95% CI = 1.91‐3.64) for combined drug‐related and suicide mortality among women and an HR of 1.42 (95% CI = 1.13‐1.79) among men comparing lost‐time to no lost‐time injuries. Circulatory disease mortality was also elevated for men with an HR = 1.25 (95% CI = 1.05‐1.50) . In contrast, we did not observe significantly different HRs between women and men, either by lost‐time injury or other measures of disability (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…4 Numerous work factors such as job strain, employment in construction and extraction occupations, unemployment and economic conditions, lack of sick days, heavy lifting, seasonal work, and workers’ compensation claims have been linked to opioid use disorder and opioid-related overdose deaths of workers. 3,59 For example, Choi reported prevalence ratios for opioid use disorder of 2.0 for psychosocial job strain and 2.2 for frequent heavy lifting. 5 Although further epidemiologic research is being conducted to examine the mechanisms of these associations, public health prevention efforts should be targeted toward working populations who face such risk factors, as part of a comprehensive response to the crisis.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that re-occurrence of incidents with a similar cause and circumstance in the workplace environment is a public health concern with unacceptable high incidence in the U.S. and worldwide [20]. Both pre-injury and post-injury correlates include social (disparity) determinants as race, and clinical conditions such as mental health disorders and drug dependence (which can be ascertained by prior ICD diagnoses) [21,22]. The Cox regression highlighted a number of conditions that affect the risk of WPI recurrence ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%